South African banks' cross-border systemic risk exposure: An application of the gas copula marginal expected shortfall - Mathias Mandla Manguzvane; John Muteba Mwamba (International Journal of Financial Studies, 2022)
Systemic susceptibility highlights the extent to which a banking sector is sensitive to negative shocks. Policymakers and regulators' objective is to avoid financial crises, and even though they can somewhat control local conditions, internationally transmitted crises are difficult to tackle. This paper analyzes the cross-border systemic risk exposure of South African banks. The marginal expected shortfall is employed with data covering 2002 to 2020. The results show that South African banks are significantly prone to crises emanating beyond the country's borders. The findings confirm the existence of a significant transfer of risk from other countries to South Africa's banking sector. Moreover, the amount of foreign capital invested in a bank is found to be a strong predictor of a bank's international exposure. Knowledge of the linkages that the banking system has with other countries, and how cross-border exposures endanger banks, will form a basis for regulations that ensure a safer financial system.
Keywords: 330; contagion; financial crisis; financial stability; mixture Copula; systemic vulnerability